Cemented all-polyethylene glenoid with standard or individualized backside curvature: a retrospective comparatie study - Schnetzke, Marc; Sulzer, Susan; Bruttel, Jennifer; Loew, Markus (Obere Extremität, 2021)
The clinical and radiographic results of an all-polyethylene glenoid with variable backside curvature adapted to the individual anatomy were compared with a standard all-polyethylene glenoid.